Investigating Changes in Cardiac Function and Structure of Left Ventricle by Speckle-Tracking Echocardiography in Patients With Hyperthyroidism and Graves' Disease - Li, Binyi; Li, Zheng; Huang, Yong (Frontiers in Cardiovascular Medicine, 2021)
Subclinical hyperthyroidism is a common thyroid dysfunction that can lead to cardiovascular complications. It is necessary to understand the treatment strategy in clinical practice. This study aimed to investigate the changes in cardiac function and left ventricular structure by speckle-tracking echocardiography in patients with hyperthyroidism and Graves’ disease. PubMed, Medline, Cochrane Library, Embase, and SinoMed were searched for targeted articles without any language restriction from inception till November 26, 2020. All studies that evaluated changes in cardiac function and left ventricular structure by speckle-tracking echocardiography in patients with hyperthyroidism and Graves’ disease were screened. Included studies met the following inclusion criteria: (1) study population diagnosed with hyperthyroidism or Graves’ disease; (2) patients without treatment who undergoing speckle-tracking echocardiography; (3) necessary data could be extracted from original studies; (4) studies published in English or Chinese; and (5) only one study from the same institution that provide detailed information or newly published article was selected if the study population was duplicated. All relevant articles from the above databases were screened and assessed according to the inclusion criteria by two reviews independently. Inverse variance methods with random-effects were employed to pool the mean differences (MDs) and the corresponding 95% confidence intervals (CIs). Ten studies with 483 patients and 434 healthy controls were included for data extraction and meta-analysis. Comparing patients with healthy controls, two-dimensional echocardiograph revealed significant differences in several parameters including interventricular septal thickness (IVST) (mean difference (MD): 0.43, 95% CI=0.12-0.73, P<0.05), and left ventricular end systolic diameter (LVEDS) (MD: 1.42, 95% CI=0.33-2.52, P<0.05). Moreover, there were significant difference in left ventricular ejection fraction (LVEF) (P<0.05), global longitudinal strain (P<0.05), and global circumferential strain (P<0.05) demonstrated by three-dimensional echocardiography. These findings suggested that left ventricle (LV) function evaluated by speckle-tracking echocardiography showed significant impairment in patients with hyperthyroidism. However, additional original studies and meta-analyses are warranted for an in-depth investigation.